Comparative analysis of qualified sportswomen, specialized in synchronized swimming, «standard» hoe-type motion kinematic characteristics - Гордєєва, М. В. (Slobozhanskyi Herald of Science and Sport, 2011)
The technics of impellent actions of the qualified sportswomen specializing in synchronized swimming is considered. The comparative analysis of existential characteristics of different kinds "standard" hoe-type the movement used in base positions of the obligatory program of synchronized swimming is presented. The structure of two kinds of "standard" fungoid movement on the basis of the comparative biokinematic analysis is established a rhythm.